Influence of scaler tip design on root surface roughness, tooth substance loss and patients' pain perception: an in vitro and a randomised clinical trial - Nur Ayman Abdul Hayei; Noor Azlin Yahya; Syarida Hasnur Safii; Roslan Saub; Rathna Devi Vaithilingam; Nor Adinar Baharuddin (BMC, 2021)
Abstract Background The influence of scaler tip design on root surface roughness, tooth substance loss and patients' pain perception is investigated. Methods This article was divided into the following parts: Part 1 Surface roughness and substance loss: an in vitro study, which involves intact extracted teeth sectioned and treated using a piezoelectric ultrasonic device (PM200 EMS Piezon, Switzerland) with a conventional scaler tip (FS-407) and a Perio Slim (PS) scaler tip (Perio Slim DS-016A). All sectioned samples for tooth surface roughness (n = 20) and tooth substance loss (n = 46) analyses were measured and compared using a 3D surface texture analyser and scanning electron microscope (SEM) respectively, at baseline and following scaling. Part 2 Pain Perception: a clinical study, which was a split mouth study design including 30 participants with gingivitis and/or mild chronic periodontitis; treated with supra-gingival scaling from teeth #13 to #23. Subjects were randomised to group A or group B. Group A was treated first with PS scaler tips, whereas group B was treated first with conventional scaler tips. Pain perception was recorded using the visual analogue scale (VAS). Results In vitro study: both scaler tips caused significant reduction in root substance roughness after scaling (p < 0.05), but no significant difference between the two scaler tips (p > 0.05) was observed. The PS scaler tip caused statistically significantly less root substance loss (p < 0.05) when the initial thickness of the tooth was < 1000 µm. Clinical study: the participants reported significantly lesser pain score during scaling using the PS scaler tip (median: 3) than when using the conventional scaler tip (median: 5) (p < 0.05). Conclusions In the in vitro study, using a slim scaler tip design causes less tooth substance loss compared to a wider scaler tip design. In the clinical study, less pain was observed compared than a wide (conventional) scaler tip design.